2022
DOI: 10.1088/1755-1315/1024/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Functional Properties of Sorghum (Sorghum bicolor (L.) Moench)-based Products and Potential Valorisation of Sorghum Bran

Abstract: Sorghum (Sorghum bicolor L. Moench) has a nutritional profile similar to rice, maize, and wheat. However, the tannin content in sorghum, which causes a slightly bitter taste, makes sorghum products less appealing to the public. Tannins can be reduced by more than 70% by grading, polishing, and soaking for 8 hours in a 0.3% of Na2CO3 solution. The tannin content in the sorghum grain and flour can be adjusted to still function as an antioxidant and has a pleasant taste. Sorghum flour has a 6-8% dietary fibre con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
(35 reference statements)
0
12
1
Order By: Relevance
“…Tannins are dominant phenolic class compounds IOP Publishing doi:10.1088/1755-1315/1169/1/012096 2 found in sorghum, acting as a dietary antioxidant. The protein content of sorghum is also higher than that of wheat [3]. Moringa leaf is also attributed to its bioactive and protein content.…”
Section: Introductionmentioning
confidence: 99%
“…Tannins are dominant phenolic class compounds IOP Publishing doi:10.1088/1755-1315/1169/1/012096 2 found in sorghum, acting as a dietary antioxidant. The protein content of sorghum is also higher than that of wheat [3]. Moringa leaf is also attributed to its bioactive and protein content.…”
Section: Introductionmentioning
confidence: 99%
“…This was presumably due to tannin content found in sorghum which responsible to intense brown color of the product [2], causing an increase in the b value. Moringa leaf also contained green pigment chlorophyll [3], which made the product had visually greenish-brown color. * Different superscripts on the same row show a significant difference at the level of = 5%…”
Section: The Color Of Dried Tapioca Noodle With Sorghum-moringa Subst...mentioning
confidence: 99%
“…Higher sorghum proportion resulted in the darker color of dried noodles, followed by a decrease in color liking score. The greenish brown color was due to sorghum's tannin content contributing to the brown color [2], and moringas' chlorophyll content contributed to the product's green color [3]. Bitterness was expected to decrease taste liking score in higher sorghum addition due to higher tannin content [2], and the glucosinolate in moringa leaf might also contribute to the products' bitterness [6].…”
Section: Sensory Acceptance Of Quality Of Dried Tapioca Noodle With S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found that in breadfruit seeds and flour, there are compounds that can cause a bitter taste, namely tannins and cyanide acid [6]. The tannin content is also a problem in the development of sorghum flour [7]. Besides causing a bitter taste, tannins have anti-nutritional properties because they can inhibit the digestion of proteins and carbohydrates.…”
Section: Introductionmentioning
confidence: 99%